Employers' Right in Set-Off as a Vindication for Non-Payment to the Contractors: A Discussion based on CIDB 2000, PAM 2006 and PWD Form 203(A) Standard Form of Contract - Lee, Chia Kuang; Noor Azlinna, Azizan (2012)
Non-payment has seriously plagued the construction industry and it severely distressed contractor's cash flow. Despite the fact that industry can only function on the basis of payment by the employers, over the years the employers had relied on the contention to set-off and use it as a basis for their refusal to pay the contractors as the amount due as shown in the payment certificates. In Malaysia, CIDB 2000, PAM 2006 and PWD Form 203(A) Standard Form of Contract are widely used to govern construction projects and manage contractual relationship between contractors and the employers. By reviewing law cases, this paper has been done to explore the magnitude of the employers in using their right in set-off as the basis for non-payment in relation to Common Law, CIDB 2000, PAM 2006 and PWD Form 203(A). The discussion and argument shows that contractors' right in payment can be deprived and challenged due to employer's right to set-off in Common law, CIDB 2000, and notably expressed in PWD Form 203(A) Standard Form of Contract. However, the employers' contention to set-off in PAM 2006 is governed under the "expressio unius est exclusio alterius" principle, whereby the set-off principle has been extinguished and only limited to what is dictated and laid out in the PAM 2006 Contract. This paper attempts to shed a light for the contractors, substantiating a platform for the contractors to understand to what extend their payment can be withheld when employers deprive their right for payment based on the allegation of set-off.